Fabrication of recyclable catalyst supports for synthesis of carbon nanofibers - Jung, HS; Kim, H; Ahn, JP; Park, JK (KOREAN INST METALS MATERIALS, 2004)
Carbon nanofiber (CNF) has been synthesized by thermal dissociation of ethylene gas in the presence of nickel catalyst. Catalyst particles of nickel were immobilized on the surface of sintered yttria-stabilized zirconia supports (YSZ support) via either direct sintering of composite compacts or chemical doping into presintered porous YSZ compacts. The effect of support microstructures on the CNF morphology was investigated. In addition, the feasibility of a recyclable support for economical synthesis of CNF was assessed.
Keywords: SEGMENTED GRAPHITE NANOFIBERS; HYDROGEN STORAGE; VOLTAMMETRY; ELECTRODES; BEHAVIOR; GROWTH; NICKEL